Conventional chemotherapy for acute myeloid leukemia: a Brazilian experience - Pagnano, Kátia Borgia Barbosa (2000)
CONTEXT: Young patients affected by acute myeloid leukemia (AML) achieve complete remission (CR) using conventional chemotherapy in about 55-85%. However, 30% of patients fail to achieve CR and the remission duration is often only about 12 months. More intensive treatment after CR seems to be necessary in order to maintain CR and obtain a definitive cure. In Brazil, few reports have been published on this important subject. OBJECTIVE: The aim of this study was to describe a Brazilian experience in the treatment of "de novo" acute myeloid leukemia (AML) in younger adult patients (age < 60 years). DESIGN: Retrospective analysis. SETTING: University Hospital, Hematology and Hemotherapy Center, State University of Campinas, Brazil. PARTICIPANTS: Newly diagnosed cases of "de novo" AML in the period from January 1994 to December 1998 were evaluated retrospectively, in relation to response to treatment, overall survival (OS) and disease free survival (DFS). Cases with acute promyelocytic leukemia (APL) were also included in this analysis. RESULTS: On the basis of an intention to treat, 78 cases of AML, including 17 cases of APL, were evaluated. The overall median follow-up was 272 days. The complete remission (CR) rate was 63.6% in the AML group (excluding APL) and 78% in the APL group. The 5-year estimated disease-free survival (DFS) was 80% for the APL group and 34% for the AML group (P = 0.02). The 5-year estimated overall survival (OS) was 52% for the APL group and 20.5% for the AML group, respectively (P = NS). Relapse was observed in 12/39 (30.7%) patients with AML and 1/11 (9%) with APL. CONCLUSIONS: These results are similar to those reported in the literature. However, relapse and mortality rates remain high, and a search for more aggressive strategies in order to prevent relapse is recommended.